Spy Glass - Snyder, Maria V. (Richmond Mira Ink, 2013)
A new legacy is rising... After siphoning her own blood magic, Opal Cowan has lost her powers and been separated from Kade and Ulrick, the two men who divide her heart. Now an outsider looking in, Opal spies through the glass on those with the powers she once had.
Keywords: Magic -- Glass art -- Fantasy fiction, American